1985
DOI: 10.1172/jci112225
|View full text |Cite
|
Sign up to set email alerts
|

Thrombomodulin is present in human plasma and urine.

Abstract: Thrombomodulin is an endothelial cell membrane protein that is a cofactor required for the rapid activation of plasma protein C. We now report that plasma and urine of normal subjects contains a modified form of thrombomodulin that is soluble. The levels measured by radioimmunoassay were 292±60 ng thrombomodulin/ml plasma and 102±38 ng thrombomodulin/ml urine. Thrombomodulin was isolated from both plasma and urine by immunoaffinity chromatography using a polyclonal anti-human thrombomodulin IgG column. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
159
1
2

Year Published

1991
1991
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(166 citation statements)
references
References 14 publications
4
159
1
2
Order By: Relevance
“…Previous reports have described the interactions between immune mucosal cells and ECs that contribute to intestinal homeostasis and intestinal epithelial permeability (19), indicating the likely presence of cross-talk between ECs and other cells expressing TM. However, a TM-soluble form, derived from the endothelial membrane, is released in plasma, but whether this form is functional is unknown (20).…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have described the interactions between immune mucosal cells and ECs that contribute to intestinal homeostasis and intestinal epithelial permeability (19), indicating the likely presence of cross-talk between ECs and other cells expressing TM. However, a TM-soluble form, derived from the endothelial membrane, is released in plasma, but whether this form is functional is unknown (20).…”
Section: Discussionmentioning
confidence: 99%
“…Soluble forms of TM derived from the extracellular domain of the molecule have been found in the plasma and urine of healthy subjects, suggesting that it is cleaved under physiological conditions. 5,41 The increase in plasma TM fragments in patients with various diseases suggests that TM release from endothelial cells is accelerated by proteolytic activity generated on the surface of the endothelium. 5 The proteases responsible for TM shedding are still unknown, although neutrophil-derived enzymes-including elastase, proteinase-3, and cathepsin G-have been implicated.…”
Section: Discussionmentioning
confidence: 99%
“…43 Several soluble TM subspecies that maintain the structure of the fourth to sixth EGF-like repeats have protein C-activating cofactor activity, although the physiological significance is obscure. 41 Whether these natural soluble TM subspecies mimic the mitogenic or angiogenic properties noted with recombinant TMD23 remains to be studied. In the present study, we demonstrated that TMD23 can promote angiogenesis in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…TM is also present as soluble heterogeneous fragments in circulating plasma and increased plasma levels of this soluble TM (s-TM) are considered to be associated with injury to endothelial cells. 10) In patients with coronary artery disease, elevated s-TM levels were found to be related to recurrent coronary events, 11) although high s-TM concentrations have been reported to be associated with a reduced risk of coronary heart disease.…”
mentioning
confidence: 99%